Boundary element method for torsional analysis - Khoo, Sane Roy. (2013)
In this paper a boundary element method is developed for calculating torsional rigidity of inhomogeneous shafts with arbitrary cross sections. One end of the shaft is attached to a fixed support and an arbitrarily distributed twisting moment is applied on the other end. Boundary element method is used to solve two-dimensional Laplace’s equation to determine warping function of certain cross section subjected to given boundary conditions in order to solve for the torsional rigidity of the shafts.